COMPARATIVE STUDY OF DIFFERENT NUTRIENT SUPPLEMENTS ON IN VITRO REGENERATION AND BOERAVINONE B PRODUCTION IN BOERHAAVIA DIFFUSA L. - S. Sharma; A. Koul; J. Sharma; V. Sharma; S. Mallubhotla1 (Journal of Animal and Plant Sciences, 2020)
Shoot cultures of medicinally acclaimed plant Boerhaavia diffusa were initiated in vitro and the influence of different strengths of Murashige and Skoog (MS) medium, plant growth regulators, carbon/nitrogen/phosphate (CNP ratio) and varying concentrations of carbon sources on biomass regeneration and boeravinone B production were analyzed. Experiments were performed to examine the effect of media manipulation strategies through HPTLC analysis on a useful secondary metabolite- boeravinone B in the plant species. MS full strength medium fortified with zeatin (Zn) (1 mg/L) and naphthalene acetic acid (NAA) (0.5 mg/L) indicated complete success with an average of 13.0 ± 0.33 shoots per explant and 10 -14 roots per explant were obtained on medium supplemented with NAA (0.5 mg/L). Well rooted plantlets were hardened and acclimatized with 95 % survival rate under green house conditions. CNP ratio of 1:1:1 (control) emerged as the best combination for biomass production (4.58 DW) in this plant species. A CNP ratio of 2:1:1 exhibited higher boeravinone B content of 16.78 %, wherein the concentration of carbon source was increased two folds. Likewise, by increasing the table sugar concentration upto 5 %, highest boeravinone B content (19.15 %) was recorded, which is 3.9 times more than that in the field grown plants. Since, sucrose (5.58 DW) and table sugar (5.63 DW) at 3 % concentration showed similar results for biomass production so sucrose in the medium could be replaced by a cheaper carbon source (table sugar) to make process cost-effective. This protocol can be used for maximizing biomass and metabolite content for its commercial exploitation and applications in herbal drug based industries.
Keywords: Carbon sources; CNP ratio; HPTLC profiling; Punarnava